Socialization of Digital Financial Applications to Organize Financial Management for Dayah Darul Hikmah Students - Afrida, Fenny; Herlambang, Albert; Marpaung, Linda Wahyu; Gea, Sanderwan Kristian; Ilham, Habibi; Halim, Hendra; Usiai, Khairil (Eastasouth Journal of Positive Community Services, 2025)
Management finance is very necessary for students, especially for for Gen Z. With existence sophistication technology there is various type common problems appeared, one of them that is problem finance. Often times for follow trend or style life, Gen Z sacrifices condition finance they are for the sake of Can follow existing trends. Such as submit credit or loan on line only For fulfil prestige life they. Activities devotion to public This was held at Dayah Darul Hikmah, Baitussalam District, Aceh Besar, on Friday, February 14, 2025, and was attended by 50 students. The activity This aiming For see how much Far students ' understanding in manage finance them and avoid from activity consumptive. Activities this also aims For make the students own guidelines in building the future they For reach stable finances. Results of activities shows an increase understanding participant related importance digitalization in management finance. The majority participant state the introduced application is very helpful in record, monitor, and analyze finance they.